RARE-18. OSTEOSARCOMA AND MEDULLOBLASTOMA IN A LI-FRAUMENI PATIENT. (5th November 2018) - Hamilton, Ronald; Razzouk, Bassem; Cudahy, Terence; Fulkerson, Daniel; Chiang, Jason; Thomas, Diana
Abstract: Li-Fraumeni patients have germline mutations in the TP53 gene resulting in increased risk of developing one or more malignant tumors. In children, osteosarcomas and rhabdomyosarcomas are the most common tumors outside the central nervous system (CNS). Primary CNS tumors in these patients include glioblastomas, choroid plexus carcinomas and medulloblastomas. We present an unusual case of a 15 year old boy who had a left tibial osteosarcoma resected 4 years ago, then treated with chemotherapy, without any recurrence or metastatic disease. His two younger male siblings both have the same mutation, and one sibling has already developed an osteosarcoma. Interestingly, the mutation is present in the mother, who has no neoplasm to date. Annual radiological studies of the CNS were normal until February 2017; but it was 13 months until the next scan, which revealed a large tumor in the lateral cerebellum. The patient was asymptomatic and a surgical resection was performed. The operative report described a well-circumscribed mass in the lateral cerebellum with little parenchymal involvement bringing up the possibility of metastatic disease. Neuropathological evaluation showed a densely cellular tumor with large and markedly pleomorphic nuclei as well as numerous mitoses. No cerebellar tissue was seen. Immunohistochemical (IHC) studies were complicated by the widely overlapping antigenicity of osteosarcomas and medulloblastomas. Next Generation Sequencing found abnormalities in SMO, DDX3X, TP53, and MYCN amplification, which are associated with SHH-activated medulloblastomas. Both GAB1 IHC and FISH studies for YAP1 were positive. In summary we report a rare case of an SHH-activated medulloblastoma, large cell/anaplastic type in a 15 year-old boy with a germline TP53 mutation and history of resected osteosarcoma.